Emission Calculations of Vehicles Used in Konya and Stages of Electric Vehicle Use - ÖZÇELİK, Abdullah Engin and KAHYAOGLU, Muhammet and ALTAN, Janset (MAS Journal of Applied Sciences, 2023)
Electric vehicles have been in our lives for a long time, but in the last two years, there has been an increase in electric vehicle sales and production. In addition to the spread of the environmental perspective day by day and the demand by wider masses, factors that will significantly affect human life, such as global warming and the decrease in fossil fuels, have become the biggest supporters of electric vehicles in the search for new technology. Emission gases created by internal combustion engines significantly affect the living space we live in. If we talk about these effects, many other components that are harmful to human and environmental health such as carbon dioxide, nitrogen oxides, sulphurous components, particles; dispersed into the air with the exhaust gas during emission. In this study, considering the damage caused by emission gases to the environment and people, we will gradually transition the internal combustion engine vehicles in Konya city center to electric vehicles in stages. In this way, we will see the significant decrease in emission gases in this study.